Examining Career Paths of Women in Educational Leadership: The Impact of Age, Gender, Maternity and Parental Leaves - Essiomle, Komla; Nadler, Leticia; ElAtia, Samira (International Journal of Education Policy and Leadership, 2024)
This study delves into the complex dynamics of leadership within Alberta’s K-12 education system, specifically focusing on the relationship between age, gender, maternity and parental leaves and women’s career progression. Using an explanatory mixed-method approach, comprising a survey of 416 educational leaders and two focus groups of 20 women in leadership roles, this research uncovers age and gender disparities in career advancement in the education system, highlighting that women often enter some leadership roles at an older age than men. Recommendations from this inquiry include a reevaluation of maternity/parental/family leave policies in schools, aligning them with principles of equitable career progression and a call for robust equity, diversity, and inclusion (EDI) policies and training at all levels of leadership and in the recruitment process.